Substrate porosity and morphological performance identify an effective growing medium for habanero pepper (Capsicum chinense Jacq. cv. Francisca) seedlings - Pandi Ariansah; Muh Agust Nur Fathoni; Krisantini; Edi Santosa (Journal of Agrosociology and Sustainability, 2026)
Background: Habanero Francisca pepper (Capsicum chinense Jacq.) is an ornamental chili cultivar whose seedling quality is strongly influenced by the composition of the growing medium. Rice husk charcoal, cocopeat, and bamboo compost are commonly used nursery substrates because they improve water retention, aeration, and nutrient availability; however, information regarding their combined use for Habanero Francisca pepper seedlings remains limited. This study aimed to identify an effective growing medium composition based on substrate physical properties and seedling morphological responses. Methods: A randomized complete block design with one factor (growing medium composition) and four treatments was applied: M0 (commercial growing medium, control), M1 (rice husk charcoal: cocopeat: bamboo compost = 2:1:1), M2 (1:2:1), and M3 (1:1:2). Substrate properties, including bulk density, particle density, and porosity, were measured. Seedling growth was evaluated through plant height, leaf number, root length, root number, total fresh weight, and total dry weight. Data were analyzed using the F-test followed by Duncan’s Multiple Range Test at the 5% significance level. Findings: The composition of the growing medium significantly affected plant height, root length, root number, total fresh weight, and total dry weight, but had no significant effect on leaf number. The M2 treatment produced the highest porosity (82.11%) and superior seedling performance, with plant height of 9.55 cm, root length of 10.36 cm, total fresh weight of 0.55 g, and total dry weight of 0.07 g, compared with 5.69 cm, 4.05 cm, 0.25 g, and 0.01 g, respectively, in the control treatment. Higher porosity in M2 likely enhanced root development and resource uptake, resulting in greater biomass accumulation. Conclusion: A cocopeat-dominant medium (1:2:1) is the most effective composition for producing high-quality Habanero Francisca pepper seedlings, supporting the use of agricultural residues as a renewable, resource-efficient alternative to commercial peat-based media in pepper nurseries. Novelty/Originality of this article: This study is the first to integrate substrate porosity assessment with morphological performance evaluation to determine an effective nursery medium specifically for Habanero Francisca pepper, a cultivar for which such information has not previously been reported.